2023
DOI: 10.3389/fphar.2023.1162036
|View full text |Cite
|
Sign up to set email alerts
|

A review of the botany, ethnopharmacology, phytochemistry, analysis method and quality control, processing methods, pharmacological effects, pharmacokinetics and toxicity of codonopsis radix

Abstract: Codonopsis Radix, a traditional Chinese medicine in China, has great medicinal and scientific value. Moreover, it can also be used as a health product in daily diet. This paper reviews the botany, ethnopharmacology, phytochemistry, analysis method and quality control, processing methods, pharmacological effects, pharmacokinetics and toxicity related to Codonopsis Radix. The information of Codonopsis Radix is obtained from scientific databases (such as Baidu Scholar, CNKI, Google Scholar, PubMed, Science Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…According to Chinese Pharmacopoeia (2020 edition) and literature, the quality markers of the TCMs included in JNNm are as follows: lobetyolin, tangshenoside I, and atractylenolide III for Codonopsis Radix; ruscogenin, methylophiopogonanone A, and ophiopogonin D for Ophiopogonis Radix; betaine for Lycii Fructus, schisandrin A, schisandrin B, schizandrol A, and schizandrol B for Schisandrae Chinensis Fructus; spinosin, jujuboside A, and jujuboside B for Ziziphi Spinosae Semen; salvianolic acid B, tanshinone IIa, cryptotanshinone, tanshinone I, and salvianic acid A Salviae Miltiorrhizae Radix et Rhizoma, respectively [12][13][14][15][16][17][18]. Except for tangshenoside I and jujuboside A, which had poor responses in this method, the above candidate quality markers of JNNm were detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chinese Pharmacopoeia (2020 edition) and literature, the quality markers of the TCMs included in JNNm are as follows: lobetyolin, tangshenoside I, and atractylenolide III for Codonopsis Radix; ruscogenin, methylophiopogonanone A, and ophiopogonin D for Ophiopogonis Radix; betaine for Lycii Fructus, schisandrin A, schisandrin B, schizandrol A, and schizandrol B for Schisandrae Chinensis Fructus; spinosin, jujuboside A, and jujuboside B for Ziziphi Spinosae Semen; salvianolic acid B, tanshinone IIa, cryptotanshinone, tanshinone I, and salvianic acid A Salviae Miltiorrhizae Radix et Rhizoma, respectively [12][13][14][15][16][17][18]. Except for tangshenoside I and jujuboside A, which had poor responses in this method, the above candidate quality markers of JNNm were detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that codonopsis is the dry root of Codonopsis pilosula (Franch.) Nannf., a plant of the Campanulaceae family, which has anti-inflammatory, antioxidant, anti-tumour, immunomodulatory, neuroprotective, and other properties (Dong et al, 2023). Li et al intervened in TNBS-induced UC rats with codonopsis extract (4.5,9,18 g/kg) for 7 days.…”
Section: Compounds Related To Nrf2 Signaling Pathwaymentioning
confidence: 99%
“…In traditional Chinese medicine, CP is often used in combination with other drugs ( Dong et al, 2023 ). It plays an important role in antioxidant, anti-gastrointestinal mucosa and anti-tumor.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…As a valuable botanical herb, CP is highly regarded for its unique medicinal value and health effects ( Dong et al, 2023 ). Sweet in flavor and neutral in nature, CP returns to the spleen and lung meridians ( Lan et al, 2023 ), and can be applied alone ( Wang J. et al, 2024 ) or used in combination with other medicines ( Zhao et al, 2024 ), its main effects include invigorating the spleen and benefiting the lungs, invigorating blood circulation and removing blood stasis.…”
Section: Introductionmentioning
confidence: 99%